1992
DOI: 10.1111/j.1432-1033.1992.tb16720.x
|View full text |Cite
|
Sign up to set email alerts
|

The ICL1 gene from Saccharomyces cerevisiae

Abstract: The glyoxylate cycle is essential for the utilization of C2 compounds by the yeast Saccharomyces cerevisiae. Within this cycle, isocitrate lyase catalyzes one of the key reactions. We obtained mutants lacking detectable isocitrate lyase activity, screening for their inability to grow on ethanol. Genetic and biochemical analysis suggested that they carried a defect in the structural gene, ICL1. The mutants were used for the isolation of this gene and it was located on a 3.1‐kb Bg/II‐SphI DNA fragment. We then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 53 publications
(23 reference statements)
1
70
0
1
Order By: Relevance
“…It thus appears that the succinate dehydrogenase complex (SDHC), a tetramer of Sdh1, Sdh2, Sdh3 and Sdh4 (Lombardo et al, 1990;Chapman et al, 1992;Bullis and Lemire, 1994;Daignan-Fornier et al, 1994), is the only TCA cycle-specific enzyme required for acetate utilization on YNBA. Our results also show that the enzymes involved in the glyoxylate cycle operation, such as ACO (Aco1) (Gangloff et al, 1990), malate synthase (Mls1) (Hartig et al, 1992;Kunze et al, 2002), isocitrate lyase (Icl1) (Fernandez et al, 1992;Taylor et al, 1996) and Mdh2 (Minard and McAlister-Henn, 1991), are indispensable for the growth of yeast cells with acetate on YNBA, regardless of their involvement in the TCA cycle. Considering that both the cytoplasmic and mitochondrial isoforms of fumarase (FUM) are encoded by a single gene, FUM1 (Wu and Tzagoloff, 1987), and that operation of the TCA cycle is dispensable on YNBA, as shown above, it is suggested that conversion of fumarate to malate Figure 6.…”
Section: Succinate-fumarate Carrier (Sfc1) Is Essential For Acetate Usupporting
confidence: 54%
See 1 more Smart Citation
“…It thus appears that the succinate dehydrogenase complex (SDHC), a tetramer of Sdh1, Sdh2, Sdh3 and Sdh4 (Lombardo et al, 1990;Chapman et al, 1992;Bullis and Lemire, 1994;Daignan-Fornier et al, 1994), is the only TCA cycle-specific enzyme required for acetate utilization on YNBA. Our results also show that the enzymes involved in the glyoxylate cycle operation, such as ACO (Aco1) (Gangloff et al, 1990), malate synthase (Mls1) (Hartig et al, 1992;Kunze et al, 2002), isocitrate lyase (Icl1) (Fernandez et al, 1992;Taylor et al, 1996) and Mdh2 (Minard and McAlister-Henn, 1991), are indispensable for the growth of yeast cells with acetate on YNBA, regardless of their involvement in the TCA cycle. Considering that both the cytoplasmic and mitochondrial isoforms of fumarase (FUM) are encoded by a single gene, FUM1 (Wu and Tzagoloff, 1987), and that operation of the TCA cycle is dispensable on YNBA, as shown above, it is suggested that conversion of fumarate to malate Figure 6.…”
Section: Succinate-fumarate Carrier (Sfc1) Is Essential For Acetate Usupporting
confidence: 54%
“…The first two enzymes, ICL and MLS, are unique to the glyoxylate cycle and are encoded by ICL1 (Fernandez et al, 1992;Taylor et al, 1996) and MLS1 (Hartig et al, 1992;Kunze et al, 2002), respectively. Icl1 is localized solely in the cytosol, even under growth conditions that induce peroxisome proliferation, and its presence in peroxisomes is not essential for a functional glyoxylate cycle (Taylor et al,154 Y. J.…”
Section: Introductionmentioning
confidence: 99%
“…Isocitrate lyase does not contain any known peroxisomal targeting signals at its C-terminal end, suggesting that the enzyme is not located in these organelles. Deletion mutants lack detectable isocitrate lyase activity and do not grow on ethanol medium demonstrating that the ICLI gene is essential for the utilization of this compound [3].…”
Section: Introductionmentioning
confidence: 99%
“…Isocitrate lyase is one of the key enzymes of the glyoxylate pathway [l]. In yeast, the enzyme is composed of four identical subunits [2] with a molecular weight of 62.5 kDa each, as deduced from the nucleotide sequence of the encoding gene [3]. Isocitrate lyase does not contain any known peroxisomal targeting signals at its C-terminal end, suggesting that the enzyme is not located in these organelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation